The Role of the Youth Sport Coach in COVID-19 - Strachan, L.; Fraser-Thomas, J.; Côté, J. (2021)
Over the past several months, the world has been faced with unprecedented times as nations, communities, and individuals have grappled with the initial shock and subsequent coming to terms with the coronavirus (COVID-19) pandemic. With respect to sport participation, many athletes and coaches are trying to cope with new realities, which continue to evolve as "return to play" platforms are released, implemented, and revisited, guided by the varied responses of governments and public health leaders around the world. In a news article published early in the pandemic (Wyman, 2020), high-performance athletes discussed their thoughts about this time, with one athlete noting that "(S)port isn`t everything" and in turn revealing the importance of athletes maintaining or developing other aspects of themselves. The statement offers some insight into the changing dynamic of sport. As researchers in the field of youth sport and positive youth development (PYD) through sport, we have been considering the impacts of this time on the present and future of youth sport programs. The field of PYD through sport focuses on the growth of positive skills that can facilitate young people`s development inside and outside of the sport context (Gould & Carson, 2008) and several models have been presented to explain positive development through sport (Fraser-Thomas et al., 2005). Within the current pandemic context, significant alterations to participation (i.e., involving quarantines, self-isolation, and physically distancing) coupled with the absence of performance opportunities (i.e., competition) must be acknowledged. This leaves coaches in unchartered territory, as they paradoxically try to balance short-term foci `in the moment`, with the long-term aims of sport engagement that may at times seem inconsequential. While we do not have all the answers as to how to approach this complex situation, we believe that coaches can best navigate these circumstances by focusing on the short-term mandate of maintaining their athletes` interest in sport, while simultaneously focusing on fostering two specific personal assets within their athletes: confidence and interpersonal connections.